2009
DOI: 10.1016/j.foodchem.2009.03.102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype and sowing date on phytostanol–phytosterol content and agronomic traits in wheat under organic agriculture

Abstract: Cereals are an important source of sterols and stanols in the human diet. The present study underlines the effect of genotype and weather conditions in bread wheat, on total sterol and stanol content (TSS), agronomic traits, proteins and ash content under organic conditions. Variations in TSS as well as other characters between two sowing dates were observed. A broad genotypic variability was also reported since extreme genotypes differed by more than 30 mg 100. g -1 DW for TSS, with total stanol content varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
(54 reference statements)
4
41
1
Order By: Relevance
“…Studies have shown that a wheat plant may stop its vegetative growth and shift towards its reproductive phase after reaching its photoperiodic requirement and that may result in shorter plant height in late sowing in Peshawar (Ahmad et al, 2005). Alignan et al (2009) reported an increase and a decrease in the number of grains per spike in wheat sown on 15 th November and delayed sowing respectively. Qasim et al (2008) documented highest grain number in crop sown on 15 th November followed by 30 th November and then 15 th December in Peshawar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a wheat plant may stop its vegetative growth and shift towards its reproductive phase after reaching its photoperiodic requirement and that may result in shorter plant height in late sowing in Peshawar (Ahmad et al, 2005). Alignan et al (2009) reported an increase and a decrease in the number of grains per spike in wheat sown on 15 th November and delayed sowing respectively. Qasim et al (2008) documented highest grain number in crop sown on 15 th November followed by 30 th November and then 15 th December in Peshawar.…”
Section: Discussionmentioning
confidence: 99%
“…Inamullah et al (2007) in Khyber Pakhtunkhwa noted 19.72% decrease in grain weight due to delay in sowing of wheat because plant does not have sufficient time to increase grain weight due to shorter photoperiod and higher temperature. Alignan et al (2009) reported that agronomic traits of wheat responded differently planted at different sowing dates. Yield components decreased due to late sowing in Australia (Asseng and Milory, 2006;Spiertz et al, 2006) and decrease in grain yield can be related to the differences in weather conditions prevailing throughout the growing season particularly during grain formation (Coventry et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reference values for each plant sterol and standard deviations (with a confidence interval of 95%) have reported in Table 5. Table 5 shows that concentration ranges of campesterol, stigmasterol and β-sitosterol in 20 Turkish bread wheat cultivars were compared with similar previously published (Clifton et al, 2004;RuibalMendieta et al, 2004;Alignan et al, 2009;Nurmi et al, 2012). Relative standard deviations (RSD) were acceptable (<6.1%).…”
Section: Quantification Of Plant Sterols In 20 Turkish Bread Wheat Cumentioning
confidence: 61%
“…Wheat is the most important food crop grown worldwide and one of the 'big three' cereal crops, with over 600 million ton being harvested annually (Valsta et al, 2004;Shewry, 2009). Bread wheat is an important source of plant sterols in the human diet (Alignan et al, 2009). Clifton et al (2004) and Valsta et al (2004) reported that even if the plant sterols level in cereals is lower than oilseeds, cereals remain the major source of natural plant sterols in the human diet due to the large amounts consumed daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation